x2-5x-6=0

Simple and best practice solution for x2-5x-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2-5x-6=0 equation:



x2-5x-6=0
We add all the numbers together, and all the variables
x^2-5x-6=0
a = 1; b = -5; c = -6;
Δ = b2-4ac
Δ = -52-4·1·(-6)
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-7}{2*1}=\frac{-2}{2} =-1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+7}{2*1}=\frac{12}{2} =6 $

See similar equations:

| -7+4v=7v-6+2 | | -5x5x5x2=500/ | | (16-5)(2)+(-1)=x | | 14-x=-22 | | 4/9h-6=23 | | 93n+6;n=1 | | −31p+79=−59p+81 | | 3x+5=-x-7* | | 4x-2(x+4)=2 | | 3x^-2x-10=0 | | -8+8p=7+3p+8p | | 18x-20x=100 | | O.25(8z-4)=z+8-2z | | -5(4x+1)=12x-3 | | -84b–10b–-81b+-62b+98b=23 | | 2x+59=10x-53 | | 1-3x=5-x | | 40=15a-5 | | 5x-2(x-5)=3(x+1)+2 | | -5p-3-6p=12-6p | | 5•(4x+7)-32=63 | | √x-6+3=10 | | 6c-8-2c=-14 | | 1/5x+5=35 | | 47b-7b-20b-15b-3=67 | | x+3=-13+3x | | 16-4=4(2p-3 | | 88z+17z-98z=56 | | 880/x=7/8 | | (a-1)(a-2)=(a+3)(a-4) | | 9x-1=6x+9x2 | | 5−9x=−76 |

Equations solver categories